Pedestrian Models for Robot Motion - Zanlungo, Francesco; Ferreri, Florent; Even, Jani; Morales, Luis Yoichi; Yücel, Zeynep; Kanda, Takayuki (Collective Dynamics, 2020)
We discuss the development of a robot system able to replicate human group motion and show how a pedestrian model may be converted to a robot control system in order to achieve this goal.